Community Social Empowerment Through Basic Food Assistance Activities Based On Lecturers And Students At The Nurul Hidayah Batam Foundation - Tito Pratama; Dailami Dailami; Moh. Thandzir; Syafruddin Rais; Wahyudi Ilham; Siska Amelia Maldin; Haufi Sukmamedian; Bojes Ariansya (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
Community Service Activities (PKM) with the title